SStrategi Pemasaran Stik Ale-Ale (Meretrix Spp) Produksi Kub Wida Mantolo Sebagai Produk Unggulan Kabupaten Ketapang - Assrorudin, Assrorudin; Fitriarni, Dian; Indriawan, Rois; Putri Dwiyanti , Agus (Politeknik Negeri Ketapang, 2024)
This study aims to identify the factors of strengths, weaknesses, opportunities, threats, and determine an effective strategy for marketing Stick Ale-Ale produced by KUB Wida Mantolo. The research uses SWOT and QSPM analysis methods. The main strength factor is that the food product is different from other UKM, with a score of 0.137, while the biggest weakness is the lack of product variety in terms of taste, with a score of 0.135. The biggest opportunity factor is that KUB Wida Mantolo uses online order services, scoring 0.241, while the biggest threat is that customers choose food products from KUB Wida Mantolo based on meticulousness, with a score of 0.220. Based on the analysis of internal and external factors, four strategies are recommended for marketing Stick Ale-Ale by KUB Wida Mantolo: (1) Utilizing e-commerce applications to expand the online market. (2) Increasing product flavor variety. (3) Partnering with online transportation services. (4) Maintaining service and product quality. The top priority result from the QSPM (Quantitative Strategic Planning Matrix) analysis is utilizing e-commerce applications, with a TAS score of 5.800.